2018
DOI: 10.38150/sajeb.7(4).p166-172
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficiency of Combined and Separated Antioxidant Supplementation of Vitamin C and E on Semen Parameters in Streptozotocin-Induced Diabetic Male Wistar Rats

Abstract: Male reproductive functions could be affected at multiple levels due to dia-betes mellitus. Antioxidants vitamins have direct impact on improving male reproductive capacity. Our objective was to assess the efficiency of treat-ment with vitamin C and E in the case of whether diabetes mellitus is the cause of infertility or if infertile men suffer from diabetes by inducing diabe-tes on male Wistar rats. Adult male Wistar rats were divided into 5 groups of 6 animals each: a normoglycemic control. Other four group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This drug is available as a synthetic analgesic since the 1970s. It is also known to have a strong antibacterial property 16,18 . Accordingly, it could be interesting to continue the investigating of this plant to ascertain and validate its medicinal value with a view to discovering new leads for better and improved management of infectious disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This drug is available as a synthetic analgesic since the 1970s. It is also known to have a strong antibacterial property 16,18 . Accordingly, it could be interesting to continue the investigating of this plant to ascertain and validate its medicinal value with a view to discovering new leads for better and improved management of infectious disease conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to the finding of Farombi et al (2008) who observed improvement in the testicular and epididymal weight of rats affected by tetracyclineinduced reproductive toxicity. Similarly, Benabbou et al (2017) also found out that vitamin C was helpful in restoring decreased testicular weight in wistar rats. The result on sperm motility showed a significant (P ≤ 0.05) decrease in the percentage sperm motility in the metronidazole group which IV).…”
Section: Discussionmentioning
confidence: 88%
“…Additionally, it has been observed to elevate blood testosterone levels (Fernandes et al, 2011;Sonmez et al, 2005). According to a study conducted by Benabbou et al (2017), the administration of Vitamin C has been found to have beneficial effects in mitigating the adverse effects of different drugs and substances on the reproductive system. Furthermore, it has been demonstrated in a study conducted by Sadeghzadeh et al (2018) that vitamin C has the ability to mitigate the detrimental impacts of dexamethasone on sperm motility, testosterone levels, and spermatogenesis indexes in mice.…”
Section: Introductionmentioning
confidence: 99%